The Role Of Village-Owned Enterprises (Bumdes) In Empowering Women's Economy In Simpang Dolok Village, Batu Bara Regency - Sitorus, Yusriadi; Fadlan, Ahmad; Faried, Annisa Ilmi (Journal of Management, Economic, and Accounting, 2026)
Women's economic empowerment in rural areas continues to face complex structural and cultural barriers, including patriarchal norms, domestic double burden, and limited access to economic resources. Village-Owned Enterprises (BUMDes) have been promoted as strategic instruments for rural community economic empowerment; however, the concrete mechanisms of their role in substantively empowering women remain insufficiently studied, particularly in the coastal regions of North Sumatra. This study aims to understand the role of BUMDes in women's economic empowerment in Simpang Dolok Village, Batu Bara Regency, through three key dimensions: access to resources, agency or participation, and control over economic achievements, drawing on Kabeer's (1999; 2005) women's empowerment framework. This study employs a qualitative approach with an intrinsic single-case study design. Data were collected through in-depth interviews, focus group discussions (FGDs), participatory observation, and documentary analysis involving 22 purposively selected informants, comprising BUMDes member and non-member women, BUMDes administrators, village officials, and husbands of key informants. The findings reveal that BUMDes "Sejahtera Bersama" has opened women's access to collateral-free business capital, skills training, and productive employment opportunities, driving an average income increase from IDR 680,000 to IDR 1,604,000 per month, representing a 135.9 percent improvement. In the participation dimension, this study identifies four forms of women's participation existing on a continuum: passive, operational, collective, and administrative-formal, with only collective participation demonstrating substantive agency transformation. In the control dimension, 62.5 percent of women hold full or partial control over their income, while 37.5 percent continue to face husbands' control over their earnings. This study also identifies a backlash phenomenon from husbands as a risk accompanying women's economic empowerment that has largely been overlooked in Indonesian BUMDes literature. Overall, BUMDes functions as an institutional arena that simultaneously transforms and reproduces gender relations, resulting in empowerment that is partial and unequal. Genuine empowerment requires interventions that not only expand economic access but also transform gender norms within households and BUMDes governance structures toward greater gender responsiveness.